Tree mycorrhizal type mediates the strength of negative density dependence in temperate forests. (1st June 2020) - Jiang, Feng; Zhu, Kai; Cadotte, Marc W.; Jin, Guangze
Abstract: Recent plant–soil feedback experiments suggest that arbuscular mycorrhizal (AM) tree species experience stronger conspecific negative density dependence (CNDD) than ectomycorrhizal (EM) tree species. Yet, how these findings inform our understanding of natural systems is limited because the roles of local soil conditions, light availability and tree species abundances in influencing CNDD for AM and EM species are not clear. Here we examined seedling and sapling survival in two temperate old‐growth forests (broad‐leaved pine and spruce‐fir forests) in Northeast China, to evaluate the effects of both conspecific and heterospecific neighbour density, as well as the soil and light environments, on the survival of AM‐ and EM‐dependent trees at early life stages. While light availability increased the survival of EM seedlings, soil organic resources increased EM sapling survival in the spruce‐fir plot. AM tree species suffered stronger CNDD than did EM tree species in both plots. In the spruce‐fir plot, soil factors and light availability mediated species CNDD but their effects differed between AM and EM species, and also between seedlings and saplings. For seedlings in both plots, we found that AM species exhibited a positive relationship between species abundance and CNDD strength, whereas this relationship was negative for EM species. Synthesis . Our results provide one of the few tests of how fungal symbioses determine species responses to intraspecific and interspecific interactions and the direct effects of local environmental conditions on seedling and sapling survival. We show that mycorrhizal type mediates the strength of CNDD and its relationship with species abundance. These results suggest that tree mycorrhizal association can determine the strength of CNDD effect on both rare and common species, and these CNDD differences are likely to influence the community composition of temperate forests. Abstract : Tree mycorrhizal type can play an important role in ecological processes. In this study, we found that arbuscular mycorrhizal tree species experienced stronger conspecific negative density dependence (CNDD) and showed a more positive CNDD‐species abundance relationship than ectomycorrhizal tree species. These results suggested that tree mycorrhizal type mediated the species interactions and abundance.